Effect of Foliar Supplementation on Enhancing Seed Yield and Final Recovery of Processed Seeds in Cotton - V SANTHY; SUNIL MAHAJAN; PR VIJAYAKUMARI; VAIBHAV CHAUDHARY (Seed Research, 2026)
A field study to evaluate effect of foliar supplementation for enhancing seed yield was conducted at ICAR-CICR experimental farm (Nagpur, Maharashtra), during kharif season for two consecutive years (2018-19 and 2019-20). The study aimed to determine the seed yield of cotton seeds in ICAR-CICR released popular G. hirsutum cotton variety, Suraj after complete processing. The experiment consisted five treatments including control laid out in RBD with three replications. Treatment comprised of foliar application of nutrients viz. T1 (recommended practice consisting spray of NAA at 45 DAS; urea at 60 DAS and KNO3 at 110 DAS); T2 (micronutrient mix), T3 (neem seed kernel extract) and T4 (fermented cow urine) each treatment applied thrice at 30 DAS, 45 DAS and 60 DAS in respective plots and T5 (water treated control). Foliar application of micronutrient mix during 2018 and neem kernel extract during 2019 proved significantly superior for the studied traits such as boll number, seed cotton yield, fuzzy seed yield and delinted, graded final clean seed yield. However, the seed recovery percentage for both the years was highest in treatment T1 (recommended) closely followed by T2 and T3. The pooled data also revealed foliar supplementation of both micro-nutrient mix and neem kernel extract as highly effective in enhancing the seed yield and, recommended practice as superior for enhanced seed recovery percentage.